Self-Regulate Learning and Al-Ghazali’s Theory of Education - Shahzadi, Mahmoona; Awan, Tajammal Hussain; Irfan, Faisal (South Asian Journal of Social Sciences and Humanities, 2021)
Al-Ghazali, the famous Muslim scholar from the 5th century presented the Theory of Education in which he defines the major goal of the mankind is to implement the shari’a which can result in the development of the best human society. The impact of society on the learning behavior of the pupil is also advocated by the Self-Regulated Learning process. This process involves the phases of observation, planning, execution and the evaluation. Zimmerman, the major contributors to the Self-Regulated Learning presented a number of shared features that were found to be already stated and asserted by Al-Ghazali. Winne & Hadwin’s Information Process Model for moving the facts from one’s temporary to the permanent memory is also the way suggested by Al Ghazali for memorizing the Holy Quran. Like the proponent of the Self-Regulated Learning, Al Ghazali also believes that the flair of knowing the facts needs a motivation. He asserts that the knowledge is always kept within the human soul and the cognitive abilities play a substantial role in granting a substantial level of inspiration and motivation for self-learning. It is better to incorporate Al-Ghazali’s contribution like the division of curriculum, categorization of knowledge, code of ethics for students, and the notion of ikhlaq in the learning process of the students for harvesting the best of results.
Keywords: Shari’a; Farz-e-Ain; Farz-e-Kafaya; Ikhlaq; Amal; Maktab; Cognition; Self-regulation